Decade-long delayed diagnosis of hypophosphatasia until next generation tooth loss: case reports on dental rehabilitation, diagnostic challenges and clinical implications - Yating Cao; Feng Zhang; Xingxing Huang; Ai Jiang; Shaoyun Jiang; Min Wu (Frontiers in Oral Health, 2025)
Hypophosphatasia (HPP) is a rare metabolic bone disorder caused by functional mutations in the gene Alkaline Phosphatase, Liver/Bone/Kidney (ALPL), resulting in impaired mineralization of bones and teeth. We report a female patient who experienced adolescent teeth loss and underwent dental rehabilitation, yet remained undiagnosed until her son developed similar symptoms before age two. Genetic testing confirmed HPP in both cases, more than a decade after her initial symptoms appeared. After multidisciplinary dental treatment, the woman's oral condition has remained stable. This case is helpful for dental professionals to enhance their understanding of HPP, thereby reducing misdiagnosis and delayed diagnosis and further preventing the intergenerational transmission of the disease. It discusses the reasons for delayed diagnosis and misdiagnosis, as well as insights into diagnostic approaches, treatment strategies and clinical implications. It emphasizes the critical need for oral professionals to enhance their understanding of HPP and to apply clinical examination methods rationally to ensure timely and appropriate diagnosis and treatment.